2017
DOI: 10.1002/ana.25071
|View full text |Cite
|
Sign up to set email alerts
|

Age, vascular health, and Alzheimer disease biomarkers in an elderly sample

Abstract: OBJECTIVE To investigate the associations between age, vascular health, and Alzheimer’s disease (AD) imaging biomarkers in an elderly sample. METHODS We identified 430 individuals along the cognitive continuum aged>60 years with amyloid-PET, Tau-PET, and MRI scans from the population-based Mayo Clinic Study of Aging. A subset of 329 individuals had FDG-PET. We ascertained presently existing cardiovascular and metabolic conditions (CMC) from healthcare records and used the summation of presence/absence of hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
123
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(138 citation statements)
references
References 51 publications
11
123
3
1
Order By: Relevance
“…There is debate on whether cardiovascular dysfunction can induce AD, because dementia related to cardiovascular conditions can happen without amyloid accumulation, as shown by the following studies: In elderly people (sample size, 942), only midlife dyslipidemia was found to be associated with amyloid deposition, rather than other risk factors including hypertension (Vemuri, Knopman, et al, 2017); and another study from the same group (sample size, 430) found that people with cardiovascular and metabolic conditions had significantly greater neurodegeneration, but their amyloid and tau were at similar levels (Vemuri, Lesnick, et al, 2017). Another follow‐up study (sample size, 322; median follow‐up, 23.5 years) found that late‐life vascular risk factors are not associated with amyloid standardized uptake value ratios (calculated from florbetapir positron emission tomography, in this case, to reflect the brain amyloid deposition).…”
Section: Systems Level Events In Aging and Admentioning
confidence: 99%
“…There is debate on whether cardiovascular dysfunction can induce AD, because dementia related to cardiovascular conditions can happen without amyloid accumulation, as shown by the following studies: In elderly people (sample size, 942), only midlife dyslipidemia was found to be associated with amyloid deposition, rather than other risk factors including hypertension (Vemuri, Knopman, et al, 2017); and another study from the same group (sample size, 430) found that people with cardiovascular and metabolic conditions had significantly greater neurodegeneration, but their amyloid and tau were at similar levels (Vemuri, Lesnick, et al, 2017). Another follow‐up study (sample size, 322; median follow‐up, 23.5 years) found that late‐life vascular risk factors are not associated with amyloid standardized uptake value ratios (calculated from florbetapir positron emission tomography, in this case, to reflect the brain amyloid deposition).…”
Section: Systems Level Events In Aging and Admentioning
confidence: 99%
“…At present, 50% of people with AD are in developing countries, which is 1 Although accumulation of Aβ peptide is considered the trigger point for neuronal degeneration, the actual pathology of AD has not been well documented. 4,5 Aggregation of amyloid fibrils can induce cell death by disrupting cellular calcium ion-homeostasis. 6 Another pathology explaining AD is selective deposition of Aβ peptide in the mitochondria of cells, which inhibits uptake of glucose by neurons and key enzyme functions.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] However, the evidence is mixed as to whether a relationship exists between vascular risk factors and Aβ burden measured concurrently in older adults, 10,12,15 with recent data from our group suggesting no relationship. 14,16,17 Additionally, a recent autopsy study identified an association between late life systolic blood pressure and tau pathology burden. 14,16,17 Additionally, a recent autopsy study identified an association between late life systolic blood pressure and tau pathology burden.…”
mentioning
confidence: 99%